2022
DOI: 10.3390/fermentation8090446
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of a Family of Sliding Mode Observers under Real-Time Conditions for the Monitoring in the Bioethanol Production

Abstract: Online monitoring of fermentation processes is a necessary task to determine concentrations of key biochemical compounds, diagnose faults in process operations, and implement feedback controllers. However, obtaining the signals of all-important variables in a real process is a task that may be difficult and expensive due to the lack of adequate sensors, or simply because some variables cannot be directly measured. From the above, a model-based approach such as state observers may be a viable alternative to sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…These types of models, however, together with the so‐called macroscopic methods, from the widely accepted extensive property equilibrium method of chemical engineering, provide the user with a convenient starting point for the analysis of microbial systems and for general purposes of design [38]. These types of models, although very simple, have been successfully applied in many studies, as well as in industry, for observation, control, and optimization purposes [1, 38]. In applying such a simplified model, one must of course be cautious when using it [39, 41].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These types of models, however, together with the so‐called macroscopic methods, from the widely accepted extensive property equilibrium method of chemical engineering, provide the user with a convenient starting point for the analysis of microbial systems and for general purposes of design [38]. These types of models, although very simple, have been successfully applied in many studies, as well as in industry, for observation, control, and optimization purposes [1, 38]. In applying such a simplified model, one must of course be cautious when using it [39, 41].…”
Section: Methodsmentioning
confidence: 99%
“…Aguilar et al [60] presented a structure with stabilizing effects on the observer performance should to the proportional gain and provides asymptotic convergence. Alvarado et al [38] implemented it in a batch fermenter under real-time conditions and demonstrated good performance:…”
Section: Proportional Sliding Mode Observer (Psmo)mentioning
confidence: 99%
See 3 more Smart Citations